2004
DOI: 10.1021/jp0402232
|View full text |Cite
|
Sign up to set email alerts
|

Ethene Adsorption, Dehydrogenation and Reaction with Pd(110):  Pd as a Carbon ‘Sponge'

Abstract: The interaction of ethene with the Pd(110) surface has been investigated, mainly with a view to understanding the dehydrogenation reactions of the molecule and mainly using a molecular beam reactor. Ethene adsorbs with a high probability over the temperature range 130 to 800 K with the low-coverage sticking probability dropping from 0.8 at 130 K to 0.35 at 800 K. The adsorption is of the precursor type, with a weakly held form of ethene being the intermediate between the gas phase and strong chemisorption. Deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 42 publications
7
51
1
Order By: Relevance
“…In order to prove this assumption we increased the carbon content of the surface and near-surface bulk regions by exposing the Pd surface to 6.0 mbar ethene at 493 K prior to reaction. At this temperature ethene decomposes and leaves a carbon-modified surface, but C atoms also migrate into surface near regions of the Pd bulk [15,16,9]. The reaction of 6 mbar ethene with 250 mbar oxygen was now repeated, starting from this 'PdC x ' surface as an initial state.…”
Section: Resultsmentioning
confidence: 99%
“…In order to prove this assumption we increased the carbon content of the surface and near-surface bulk regions by exposing the Pd surface to 6.0 mbar ethene at 493 K prior to reaction. At this temperature ethene decomposes and leaves a carbon-modified surface, but C atoms also migrate into surface near regions of the Pd bulk [15,16,9]. The reaction of 6 mbar ethene with 250 mbar oxygen was now repeated, starting from this 'PdC x ' surface as an initial state.…”
Section: Resultsmentioning
confidence: 99%
“…The more intense peak at 284.2 eV is assigned to a surface CH x (x=0-3) species formed from the dissociation of an ethylenic and/or acetate species. The features at 285.5 and 288.0 eV are assigned to CO and an acetate species, respectively [19][20][21][22].…”
Section: Xpsmentioning
confidence: 99%
“…Madix et al [25], have reported that the saturation coverage for CO on Pd(100) at room temperature is 0.53 ML. By comparing the peak area of the C 1s is [19] and acetic acid [26] to be approximately 1.5 ML. These authors report that of this 1.5, 0.5 ML is on the topmost surface while the remainder is interdiffused into the top several layers of the catalyst [18,19,26].…”
Section: Xpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, its existence was proven for the PtA C H T U N G T R E N N U N G (110) [5] and PdA C H T U N G T R E N N U N G (110) [6] surfaces. Theoretical work on subsurface carbon is relatively scarce as well.…”
mentioning
confidence: 99%